Perancangan Alat Pengendali Pompa Air Untuk Filtrasi Kejernihan Air Kolam Ikan Menggunakan Mikrokontroler Wemos D1 R1 Berbasis IoT - yudi Irawan Chandra; Fitri Sjafrina; Pipit Dewi Arnesia (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research aims to develop a water pump control system that can improve the filtration efficiency of fish pond water clarity using the Wemos D1 R1 microcontroller based on Blynk. The success of fish pond water filtration is very important for the health and survival of fish. This system is designed to monitor and control the water pump automatically based on water quality parameters such as temperature, pH, and turbidity level. The Wemos D1 R1 microcontroller is used as the brain of the system which is connected to water quality sensors and utilizes the Blynk platform to monitor and control remotely via mobile devices. The research method involves the development of synergistically integrated hardware and software. Test results show that the system is able to effectively maintain stable fish pond water quality, improve filtration, and optimize water pump usage. With remote control through the Blynk app, fish pond owners can monitor and manage the system more easily and efficiently. This research makes a significant contribution to the application of automation technology to improve fish pond water quality management, making it more efficient and sustainable.